Strategic human resource management: maintaining a competitive advantage in virtual organization / Mahathir Mahali, Junaidah Jamaluddin, Zaihan Usman @Othman - Mahali, Mahathir; Jamaluddin, Junaidah; Usman @Othman, Zaihan (2005)
HRM is the effective management of people at work. HRM primarily resides in the people and reward subsystems. This means that HRM systems should be aligned with the strategy, processes and structure of the organization. By running all the human resource function, the organization will not face any trouble even if the function is influenced by the external and internal environment such as culture, global and technologies. Coordinating and managing the whole systems of HRM with the implementation of strategic thinking are called Strategic Human Resource Management (SHRM). This paper, therefore, will be discussing the major SHRM's activities and the implementations of virtual organization as one of a strategic planning in order to stay competitive in the era of rapidly changing organization.